Use of the Scilab® Free Software for Physical Evaluation of Green and Roasted Coffee arabica L. - Oliveira, Emanuelle Morais de; Godoy, Helena Teixeira; Silva, Itallo Dirceu Costa; Filho, José Teixeira (Food Science and Agriculture: Research Highlights Vol. 2, 2025)
Background: The evaluation of coffee quality before and after the roasting process is a determining factor for defining and evaluating coffees. Among the parameters analysed, physical and chemical characterisation are considered extremely important, since from them the quality of the beverage from these coffees can be predicted. Aim: This chapter focuses on the comprehensive analysis of the physical and chemical parameters of coffee samples categorised as soft, hard, and rio beverages. Methods: The physical evaluation considers key attributes such as bean type, sieve size, and colour. In addition to the physical assessment, a detailed chemical analysis was conducted to evaluate essential compositional factors that impact the coffee’s overall quality and flavour profile. This includes determining the moisture content, ethereal extract, and protein levels, which are essential for Maillard reactions during roasting. Furthermore, the study examines ash content, soluble solids, and total titratable acidity. The coffee samples were roasted at different roasting levels specific to each beverage category to evaluate how varying roasting intensities influence their physical and chemical properties. During the roasting process, critical parameters such as colour development and mass loss were carefully monitored utilising the free software Scilab®. Results: The results obtained for the Rio beverage coffees presented lower physical classifications compared to other coffee types, with these coffees exhibiting a lighter colour and, regarding the sieve, showed a higher percentage of larger, flat beans, which may influence the texture and extraction characteristics of the brewed coffee. The moisture content was found to be in compliance with current regulations, ensuring proper storage and roasting conditions. The ether extract, protein levels, and ash content were all within the expected ranges, indicating that the chemical composition of the Rio coffee samples was consistent with standard quality expectations. The Rio beverage coffees exhibited the lowest soluble solids content and the highest total titratable acidity compared to the other types of coffee. Upon roasting, the colour parameters -L* (lightness), b* (yellow-blue chromaticity), C* (chroma, or colour saturation), and H* (hue angle) - decreased as the roasting level increased, indicating that the coffee beans darkened and became less vibrant in color. Additionally, mass loss increased with higher roasting levels, which is consistent with the typical reduction in moisture content and other volatile compounds during the roasting process. But no difference was observed between the beverages. The compiled graphs illustrated a clear distinction among the samples, within the scope of each roast. This suggests that the roasting process produced consistent and distinguishable changes in the physical properties of the beans, reinforcing the effectiveness of the analytical methods used. Conclusion: Among the various parameters analysed, the L* colour parameter (lightness) was the most effective in differentiating the samples. Its strong correlation with roasting intensity highlights its significance in determining the roasting point.